CEU Graduation Ceremony 2000, Pesti Vigado
Recording of the graduation ceremony of the class of 1999/2000 in the Budapest's Vigadó Concert Hall in June 2000. Introductory words by Academic Pro-Rector of CEU Stefan Messman and Rector of the CEU Yehuda Elkana. In addition to the conferring of degrees upon the Class of 2000, the ceremony featured a Commencement Address by Nobel Prize-winning author Wole Soyinka as well as the presentation of the Central European University Open Society Prize to Hungarian President Árpád Göncz by CEU Founder George Soros.